IADC/SPE Drilling Conference 1994
DOI: 10.2118/27448-ms
|View full text |Cite
|
Sign up to set email alerts
|

Universal Fluid: A Drilling Fluid to Reduce Lost Circulation and Improve Cementing

Abstract: A universal fluid (UF) is typically a water-base fluid that has been treated with finely ground blast furnace slag and that still maintains the appropriate characteristics of a good drilling fluid. The slag becomes concentrated in the filter cake formed while drilling permeable formations and slowly sets to form a hard layer intimately bonded to the formation. True zonal isolation can be obtained by using a UF and subsequently cementing with slag-based mud solidification technology. Complete mud displacement a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 3 publications
0
5
0
1
Order By: Relevance
“…The formation of many holes in a hydrated cement matrix and the lubrication effect of the oil phase lead to a reduction in strength and an increase in the porosity. Nahm et al (1994), and Hale and Cowan (1991) reported the conversion of designed drilling fluid to cement adding blast furnace slag. This special drilling fluid called universal fluids (UF) was a water-based fluid that would be activated by alkaline materials such as caustic soda and soda ash.…”
Section: Chemical Incompatibility Of Plugging Materials and Drilling ...mentioning
confidence: 99%
“…The formation of many holes in a hydrated cement matrix and the lubrication effect of the oil phase lead to a reduction in strength and an increase in the porosity. Nahm et al (1994), and Hale and Cowan (1991) reported the conversion of designed drilling fluid to cement adding blast furnace slag. This special drilling fluid called universal fluids (UF) was a water-based fluid that would be activated by alkaline materials such as caustic soda and soda ash.…”
Section: Chemical Incompatibility Of Plugging Materials and Drilling ...mentioning
confidence: 99%
“…Therefore proper yard/field tests are required to assess this option. For permanent deployment we advocate "cementing" of the coiled tubing in place by means of Shell's Universal Fluid (Nahm et al, 1994) that is used as a drilling fluid but later turns into solid material (Figure 7).…”
Section: Seismic Array Inside Coiled Tubingmentioning
confidence: 99%
“…Innovaciones en los procesos de cementación de pozos petroleros ha llevado a la utilización de escoria de alto horno para contrarrestar los problemas surgidos durante la cementación de pozos horizontales, minimizando los problemas de recirculación y facilitando la operación tradicional (6)(7)(8)(9). Algunos trabajos indican que la utilización de un fluido de perforación universal que contenga escoria granulada de alto horno como adición (entre un 25 y un 35%); además del empleo de lechadas de cemento con un porcentaje de reemplazo variable de escoria granulada (entre un 20 y un 40%) (6-9) han sido casos exitosos.…”
Section: Introductionunclassified
“…This has minimised recirculation problems and facilitated traditional well operation (6)(7)(8)(9). A number of authors have proposed the use of a universal drilling fluid containing granulated blast furnace slag as an addition (at rates of from 25 to 35%).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation